If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 4x + 6 = 8x Reorder the terms: 14 + 6 + 4x = 8x Combine like terms: 14 + 6 = 20 20 + 4x = 8x Solving 20 + 4x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 20 + 4x + -8x = 8x + -8x Combine like terms: 4x + -8x = -4x 20 + -4x = 8x + -8x Combine like terms: 8x + -8x = 0 20 + -4x = 0 Add '-20' to each side of the equation. 20 + -20 + -4x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -4x = 0 + -20 -4x = 0 + -20 Combine like terms: 0 + -20 = -20 -4x = -20 Divide each side by '-4'. x = 5 Simplifying x = 5
| -19x+23y=-3 | | 3x+14x+2=19 | | -4p+15=-15 | | =5(x+3)+3(y+1) | | 5x-3(x-4)=-5+4x+13 | | (x+8)(x-7)=16 | | 0=-16t^2+20t+40 | | -4w-4= | | 99-4s-6s=-9 | | 9=b | | y=xcos(x) | | 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 | | c-80=36 | | X=38-(-x) | | 3(x+4)-(x+5)=x+4 | | =7+4(x+5) | | f=6q-4 | | -23b=35b | | .23x+.45=8-.32x | | 3x+-7+2x=9 | | 3x-8=5x+3 | | 18x^2-25x=-8 |